DETERMINANTS PREDICTOR OF USED HIV TESTING SERVICE AMONG UNIVERSITY STUDENTS IN NORTHERN - Pinyaphong, Jakkrite (Phranakhon Rajabhat Research Journal : Humanities and Social Sciences, 2020)
The purpose of this research was to study the factors predicting the HIV testing service used among northern university students. The sample groups derived from systematic random sampling were 721 subjects. The online questionnaire was developed based on the review of the previous research studies and consistency reliability of Cronbach’s alpha coefficient was 0.81-0.89. The data were subsequently analyzed by using descriptive statistic and logistic regression. The results revealed that university students experienced HIV testing service used only 10.3% and in last year had sexual risk behaviors due to inconsistent condom use 50.4%, having more than 1 partner 27.4%. Factors that predict HIV testing service’s used of university students were low self-esteem of HIV infected people (adjusted odds ratio [AOR]= 6.43; 95% CI=2.15-19.17), lovers encouraging for HIV testing (adjusted odds ratio [AOR] =6.07; 95% CI=1.83-20.04), HIV testing represented the responsibility (adjusted odds ratio [AOR] =6.05; 95% CI=2.04-17.91), if infected with HIV will lose friends (adjusted odds ratio [AOR] =4.77; 95% CI=1.15-19.83), It is inconvenient to access HIV services (adjusted odds ratio [AOR] =2.95; 95% CI=1.03-8.15), aged over than 20 (adjusted odds ratio [AOR] =2.76; 95% CI=1.15-6.65), male (adjusted odds ratio [AOR] =2.03; 95% CI=1.24-3.32). In addition, the samples intended to get HIV testing 62.4%. The finding will be used to design intervention to change attitudes towards HIV testing and design the appropriate services that are suitable with the needs of the university students.